Operation management and data analysis for an indoor vertical farming system - Eng, Joshua Zhi Heng (Nanyang Technological University, 2024)
In response to the challenges posed by increased urbanization, which has significantly reduced available land for agriculture, and leveraging advancements in technology, Indoor Vertical Farming Systems (IVFS) have emerged globally as a sustainable solution. These systems aim to enhance crop yield per square meter, ensuring substantial harvests despite spatial constraints. Additionally, IVFS offer the advantage of a controlled growth environment, facilitating higher quality and faster crop production compared to traditional farming methods. A critical aspect of maximizing the potential of IVFS involves providing users with comprehensive data to analyse and make informed decisions that boost crop yields. Consequently, this project focuses on developing a dashboard designed to present IVFS data in an accessible manner. The primary objectives include enhancing the dashboard’s user interface (UI), user experience (UX), and functional capabilities. Through the strategic use of data visualization techniques, the dashboard aims to simplify data analysis, enabling more efficient decision-making processes. This report delves into the benefits of IVFS, the role of dashboards and data visualization in optimizing these systems, and the specific enhancements made to the dashboard. Following the implementation of these improvements, thorough testing was conducted to verify functionality and identify areas for further refinement. The report concludes with a discussion on future directions for enhancing the dashboard, outlining potential strategies to further enrich the IVFS data analysis experience.